2010
DOI: 10.1590/s1809-48722010000400004
|View full text |Cite
|
Sign up to set email alerts
|

Ausculta cervical em adultos sem queixas de alteraçãona deglutição

Abstract: Introduction:Cervical auscultation is a noninvasive test in the noisy swallowing pharyngeal stage. Objective:To verify the sounds of swallowing, the time of its occurrence based on subjective examination of cervical auscultation. Method:Cross-sectional study, clinical and experimental agreement in which participated thirty and two female adults young, mature swallowing pattern. The examination included the orofacial analysis of the orofacial, associated with cervical auscultation of both sides and compared the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
(15 reference statements)
0
3
1
Order By: Relevance
“…The average duration of swallowing apnea (dA) was getting longer, according to the volume swallowed. The time measured was not influenced by age 27 , differently from that verified in previous studies using a different methodology 13,23,28 . Regarding gender, only in relation to the rate obtained through the ratio T/ dA in 5 ml swallows it should be taken into account the individual's gender, since men presented higher rates than women 27 .…”
Section: Correspondence Of Swallowing Sounds With Physiological Eventscontrasting
confidence: 82%
See 2 more Smart Citations
“…The average duration of swallowing apnea (dA) was getting longer, according to the volume swallowed. The time measured was not influenced by age 27 , differently from that verified in previous studies using a different methodology 13,23,28 . Regarding gender, only in relation to the rate obtained through the ratio T/ dA in 5 ml swallows it should be taken into account the individual's gender, since men presented higher rates than women 27 .…”
Section: Correspondence Of Swallowing Sounds With Physiological Eventscontrasting
confidence: 82%
“…In this study, the functional assessment of swallowing with 32 women was performed, with a mean age of 25.84 years. In addition, the study showed that the time for swallowing solids was longer in older subjects 28 . This increased duration of pharyngeal transit associated to the increase of age, was also reported in other studies, and should be considered in clinical practice 13,23 .…”
Section: Correspondence Of Swallowing Sounds With Physiological Eventsmentioning
confidence: 92%
See 1 more Smart Citation
“…Clinical signs were observed and taken note of, including anterior oral escape, oral residue (rest of the consistency observed in the oral cavity with direct inspection), hawking, wet voice (observed with the production of the prolonged "a" vowel after swallowing the volume), coughing, choking, watering eye, respiratory changes, and cervical auscultation changes (presence of or increase in noise). In the cervical auscultation assessment 11 , the stethoscope used was the Littmann Cardiology III. The auscultation was performed on the lateral region of the trachea, above the cricoid cartilage.…”
Section: Clinical Assessmentmentioning
confidence: 99%